After Silent Revolution: Most Marginalized Dalits and Local Democracy in Uttar Pradesh, North India. (June 2017) - Kumar, Satendra
There exists a widely held view that a 'silent revolution' is occurring in North India. However, a scanty literature deals with how this revolution has changed the distribution of political opportunities on the ground. Drawing on longitudinal and long-term ethnographic research conducted between 2005 and 2015 in a village and its region, western Uttar Pradesh (UP), this article uncovers the complex and contradictory processes of change taking place in the nature of caste and its politicization in contemporary India. By focusing on different caste groups, this article examines the ways in which these groups are responding to recent political changes, particularly in the wake of the extension of reservations in Panchayati Raj Institutions (PRIs) and the political rise of the Bahujan Samaj Party (BSP) in the state of UP. This article shows that there has been a marked change in the relations of domination and subordination between upper castes and the Other Backward Classes (OBCs), and the Dalits in the region. However, I argue that despite radical changes in the rural power structure of UP, many Dalit groups remain marginal in local politics and social life. The emerging caste groups such as Jatavs within the Dalits refuse to give space to the aspirations of the most marginalized groups.